Fragmentation in mitochondrial genomes in relation to elevated sequence divergence and extreme rearrangements - Shiqian Feng; Andrea Pozzi; Vaclav Stejskal; George Opit; Qianqian Yang; Renfu Shao; Damian K. Dowling; Zhihong Li (BMC Biology, 2022)
Abstract Background A single circular mitochondrial (mt) genome is a common feature across most metazoans. The mt-genome includes protein-coding genes involved in oxidative phosphorylation, as well as RNAs necessary for translation of mt-RNAs, whose order and number are highly conserved across animal clades, with few known exceptions of alternative mt-gene order or mt-genome architectures. One such exception consists of the fragmented mitochondrial genome, a type of genome architecture where mt-genes are split across two or more mt-chromosomes. However, the origins of mt-genome fragmentation and its effects on mt-genome evolution are unknown. Here, we investigate these origin and potential mechanisms underlying mt-genome fragmentation, focusing on a genus of booklice, Liposcelis, which exhibits elevated sequence divergence, frequent rearrangement of mt-gene order, and fragmentation of the mt genome, and compare them to other Metazoan clades. Results We found this genus Liposcelis exhibits very low conservation of mt-gene order across species, relative to other metazoans. Levels of gene order rearrangement were, however, unrelated to whether or not mt-genomes were fragmented or intact, suggesting mitochondrial genome fragmentation is not affecting mt-gene order directly. We further investigated possible mechanisms underpinning these patterns and revealed very high conservation of non-coding sequences at the edges of multiple recombination regions across populations of one particular Liposcelis species, supportive of a hypothesis that mt-fragmentation arises from recombination errors between mt-genome copies. We propose these errors may arise as a consequence of a heightened mutation rate in clades exhibiting mt-fragmentation. Consistent with this, we observed a striking pattern across three Metazoan phyla (Arthropoda, Nematoda, Cnidaria) characterised by members exhibiting high levels of mt-gene order rearrangement and cases of mt-fragmentation, whereby the mt-genomes of species more closely related to species with fragmented mt-genomes diverge more rapidly despite experiencing strong purifying selection. Conclusions We showed that contrary to expectations, mt-genome fragmentation is not correlated with the increase in mt-genome rearrangements. Furthermore, we present evidence that fragmentation of the mt-genome may be part of a general relaxation of a natural selection on the mt-genome, thus providing new insights into the origins of mt-genome fragmentation and evolution.